The relationship between fibrosis and nodule structure and esophageal varices - Coşar, Arif Mansur; Yakar, Tolga; Serin, Ender; Özer, Birol; Kayaselçuk, Fazilet (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: The aim of the present study was to evaluate the histopathological findings of cirrhosis together with clinical and laboratory parameters, and to investigate their relationship with esophageal varices that are portal hypertension findings. Materials and Methods: A total of 67 (42 male and 25 female) patients who were diagnosed with cirrhosis were included in the study. The mean age of the patients was 51.6±19.0 (1-81) years. The biopsy specimens of the patients were graded in terms of fibrosis, nodularity, loss of portal area, central venous loss, inflammation, and steatosis. The spleen sizes were graded ultrasonographically, and the esophageal varices were graded endoscopically. Results: In the multivariate regression analysis, there was a correlation between the advanced disease stage (Child-Pugh score odds ratio (OR): 1.47, 95% confidence interval (CI): 1.018-2.121, p=0.040), presence of micronodularity (OR: 0.318, 95% CI: 0.120-0.842, p=0.021), grade of central venous loss (OR: 5.231, 95% CI: 1.132-24.176, p=0.034), and presence of esophageal varicose veins. Conclusion: Although thrombocytopenia and splenomegaly may predict the presence of large esophageal varices, cirrhosis histopathology is the main factor in the presence of varices. Cite this article as: Coşar AM, Yakar T, Serin E, Özer B, Kayaselçuk F. The relationship between fibrosis and nodule structure and esophageal varices. Turk J Gastroenterol 2019; 30(7): 624-9.